Micromachined mmWave 28.0/38.0 GHz MIMO antenna loaded with frequency selective surface for gain enhancement and SAR analysis for future wireless applications - Manish Sharma; Bhaskara Rao Perli; Geetanjali Singla; Tathababu Addepalli; Sivasubramanyam Medasani; B. Satya Sridevi; Tanweer Ali (PLoS ONE, 2026)
The presented work describes the four-port multiple-input multiple-output (MIMO) antenna designed on Rogers substrate with a thickness of 0.787 mm. The core of the MIMO antenna includes a hexagonal-patch etched by a rectangular slot and an etched hexagonal-ring in full-ground, which are printed on opposite surfaces, generating measured millimeter-wave (mmWave) bandwidth of 26.45 GHz-29.27 GHz and 37.04 GHz-39.12 GHz. The dielectric material is micromachined, and the four-port radiating elements maintain isolation of more than 20.0 dB with an overall size of 17.0 mm × 22.0 mm × 0.787 mm. The novel 11 × 11 hexagonal-ring frequency-selective-surface (FSS) is placed below the MIMO antenna, enhancing the peak-gain by 5.16 dBi with a size of 42.50 mm × 42.50 mm printed on Rogers5880 0.787 mm thickness. The MIMO antenna also features good diversity-performance with ECC mmWave-FSS < 0.18, DG mmWave-FSS > 9.995 dB, TARC mmWave-FSS < −4.76 dB, and CCL mmWave-FSS < 0.30 b/s/Hz. The cumulative features with dual millimeter wave bands, enhanced peak-realized gain, suppressed back-lobe radiations, and good diversity performance make the proposed MIMO antenna loaded with FSS suitable for 5G, satellite-communication, IoT, and smart cities applications. The MIMO antenna loaded with FSS is also subjected for SAR analysis for input power of 50 mW and 500 mW.